Seroepidemiological investigation of SARS-CoV-2 infection and risk factors in Indonesia before mass COVID-19 vaccination - Wahyono, Tri YM.; Mahkota, Renti; Nurcandra, Fajaria; Ansariadi, Ansariadi; Hidajah, Atik C.; Helda, Helda; Syahrul, Fariani; Dwinata, Indra; Kawi, Nurhayati (Narra J, 2025)
At the onset of the coronavirus disease 2019 (COVID-19) pandemic in Indonesia, surveillance focused on finding and treating symptomatic cases. However, emerging evidence indicated that asymptomatic and pre-symptomatic individuals significantly contributed to viral transmission. This highlights the need for comprehensive surveillance to understand better the actual spread of SARS-CoV-2. Therefore, the aim of this study was to determine the seroprevalence of SARS-CoV-2 antibodies in the general population across Indonesia and identify risk factors associated with infection at the beginning of the pandemic. A cross-sectional survey was conducted across 17 provinces, 69 districts/cities, and 1,020 villages in Indonesia from December 22, 2020, to February 15, 2021. A multistage random sampling technique was employed. Serological testing using enzyme-linked immunosorbent assay (ELISA) was performed to detect anti-SARS-CoV-2. Complex sample analysis, adjusted for weights, was utilized to estimate the national seroprevalence and a generalized linear model with a binomial distribution was applied to identify risk factors. A total of 10,161 individuals were included in the final analysis, with the national seroprevalence being 14.8% (95% confidence interval (CI): 14.2–18.5). The prevalence was higher in females (16.8%; 95%CI: 12.5–22.3), individuals aged 46–59 years (18.6%; 95%CI: 14.2–24.0), and in urban areas (20.1%; 95%CI: 15.0–26.2). The highest prevalence was observed in North Maluku (35.6%; 95%CI: 29.3–42.5). Notably, 54.2% of seropositive individuals were asymptomatic, while 7.5% reported hypertension as a comorbidity. Factors associated with higher seroprevalence were being married (adjusted prevalence ratio (aPR): 1.47; 95%CI: 1.02–2.12), widow (aPR: 1.74, 95%CI: 1.01–3.00), and close contact with confirmed cases (aPR: 2.04; 95%CI: 1.52–2.73). This study revealed a COVID-19 prevalence significantly higher than official estimate in Indonesia, underscoring the need for improved surveillance system to more accurately track disease spread and to inform timely public health responses in the future.